Legong Keraton in the Perspective of Balinese Artists - Ni Nyoman Sudewi (Institut Seni Indonesia Denpasar, 2023)
Legong Keraton, one of the most influential Balinese dance genres in the growth of dance in Bali, has existed since the end of the nineteenth century. This dance has undergone three eras in Balinese culture, starting from the reign of kings, Dutch colonialism, and post-independence of Indonesia. The objective of this study is to find out how Balinese artists construe the existence of Legong Keraton. As a performing art, Legong appears in multiple layers and requires a multidisciplinary approach. The ethnochoreological approach, considered as a multidisciplinary approach, was implemented to examine objects from various aspects to obtain a complete and comprehensive understanding. The author carried out this qualitative study in procedural systematic manner including literature review, informant determination and interview, field observation, data sorting, and analysis. The results of the study indicate that Legong Keraton acts as a milestone in changing form of Balinese dance as a source of inspiration for the creation of works of art as well as a means of education. Furthermore, as a learning material, Legong Keraton has unique form and transmission method. Balinese artists consider Legong Keraton as a traditional art carrying the identity of Balinese dance that make it deserve to be appreciated and preserved.